High Survivorship With Cementless Stems and Cortical Strut Allografts for Large Femoral Bone Defects in Revision THA - Kim, Young-Hoo (Clin Orthop Relat Res, 2015)
BACKGROUND: Numerous studies have investigated the clinical and radiographic results of revision THAs with use of cementless stems and cortical strut allografts. However, to our knowledge, no long-term followup studies have evaluated patients undergoing revision THA with use of cortical strut allografts where the allografts provided the primary stability for extensively coated femoral stems in the presence of extensive femoral diaphyseal bone defects. QUESTION/PURPOSES: We performed this study to determine (1) validated outcomes scores; (2) radiographic signs of fixation and allograft healing; (3) frequency of complications; and (4) survivorship of the components after use of cortical strut onlay allografts in Types IIIB and IV femoral diaphyseal bone defects. METHODS: Between 1994 and 2003, we performed 140 revision THAs in 130 patients with Paprosky Types IIIB and IV femoral diaphyseal defects. The patients were treated using extensively coated femoral stems and cortical strut allografts because primary axial or rotational stability could not be achieved without grafting. Ten of the patients (10 hips; 7.7%) were lost to followup or died before 10 years; the remaining 120 patients (130 hips) represent the study group in this retrospective study. There were 66 men and 54 women. Their mean age at the time of index surgery was 59 ± 18 years (range, 36–67 years). The primary diagnosis was predominantly osteonecrosis of the femoral head (53%). The most common reason for revision was aseptic loosening (97%), followed by periprosthetic fracture (3%). The mean time from primary to revision THA was 12 years (range, 8–27 years). The mean duration of followup was 16.1 years (range, 12–20 years). RESULTS: The mean Harris hip score was 39 ± 10 points before revision and improved to 86 ± 14 points at 16 years followup (p = 0.02). The mean preoperative WOMAC score was 62 ± 29 (41–91) points and improved to 22 ± 19 (11–51) points at 16 years followup (p = 0.003). Of the 130 stems, 113 (87%) had bone ingrowth, five (4%) had stable fibrous ingrowth, and 12 (9%) were unstable. All allografts were incorporated. Four hips (3%) had a displaced femoral shaft fracture at the stem tip; four (3%) had a postoperative dislocation; and six (5%) had early postoperative infection. Kaplan-Meier survivorship analysis, with revision or radiographic failure as the endpoint, revealed that the 16-year rate of survival of the components was 91% (95% CI, 0.88%–0.96%). CONCLUSION: Supportive cortical strut onlay allografts provided high survivorship beyond 12 years of followup in revision THAs. Future studies might compare this approach with allograft-prosthesis composites, proximal femoral replacement, or modular fluted, tapered stems. LEVEL OF EVIDENCE: Level IV, therapeutic study.